Effect of high-intensity interval training versus small-sided games training on sleep and salivary cortisol level - Bonato, M.; La Torre, A.; Saresella, M.; Marventano, I.; Merati, G.; Banfi, G.; Vitale, J. A. (International Journal of Sports Physiology and Performance, 2020)
Purpose: The authors compared sleep quality and salivary cortisol concentration after high-intensity interval training (HIIT) and small-sided games (SSGs) performed at the habitual training time in nonprofessional male soccer players. Methods: A total of 32 players (age = 24 [6] y, height = 1.77 [0.06] m, and body mass = 75 [12] kg) were randomized into an HIIT group or an SSG group. Actual sleep time, sleep efficiency (SE), sleep latency, immobility time (IT), moving time (MT), and fragmentation index were monitored using actigraphy before (PRE) and 2 nights after (POST 1 and POST 2) the training session. Salivary cortisol levels were measured before (PRE) and after (POST) training. Cortisol awakening response was evaluated. Results: Significant intragroup differences in the HIIT group were noted for actual sleep time (P < .0001), SE (P < .0001), sleep latency (P = .047), IT (P < .0001), MT (P < .0001), and fragmentation index (P < .0001) between PRE and POST 1 and for SE (P = .035), IT (P = .004), MT (P = .006), and fragmentation index (P = .048) between PRE and POST 2. Intergroup differences for actual sleep time (P = .014), SE (P = .048), IT (P < .0001), and MT (P = .046) were observed between the HIIT and the SSGs group at POST 1 were detected. Significant intragroup variations were observed in PRE and POST salivary cortisol levels (P < .0001 for HIIT; P = .0003 for SSGs) and cortisol awakening response (P < .0001 for HIIT; P < .0001 for SSGs). Significant intergroup differences between the HIIT and the SSGs group were found at POST (P < .0001) and in cortisol awakening response (P = .017). Conclusions: Changes in actigraphy-based sleep parameters and salivary cortisol levels were greater after an acute session of HIIT than SSGs in this sample of nonprofessional male soccer players.